Comparison of thiol disulfide values in the cord blood of patients undergoing cesarean section under spinal or general anesthesia: Effects of anesthesia on thiol disulfide levels in cord blood - Soysal, Çağanay; Soysal, Yalçın; Döğer, Cihan; Yılmaz, Elif; Özdemir, Oğuz; Küçüközkan, Tuncay; Erel, Özcan (Journal of Surgery and Medicine, 2022)
Background/Aim: Oxidative stress is known to increase in patients receiving anesthesia before undergoing surgery. Since newborns are more sensitive to oxygen-free radicals, the effects and characteristics of anesthesia methods that are used for pregnant women require analysis. This study aimed to evaluate the effects of spinal and general anesthesia on oxidative stress by investigating thiol disulfide and ischemia modified albumin (IMA) concentrations in the cord blood of patients undergoing cesarean section (C-section) via spinal or general anesthesia. Methods: This cross-sectional prospective study included 60 patients who were indicated for elective cesarean section. Patients with chronic disease, pregnancy complications and/or required emergency cesareans were not included. Group 1 (n = 30) underwent general anesthesia, and Group 2 (n = 30) underwent spinal anesthesia during their C-sections. Thiol–disulfide levels were evaluated concurrently in all blood samples taken from the umbilical artery remaining on the placental side. Results: The mean age (SD) of the mothers was 30.6 (4.4) years and the mean gestational age (SD) was 39.0 (0.9) weeks. Gestational age, birth weight, and first and fifth min Apgar scores of the two groups were similar. The mean (SD) native thiol (362.4 [63.8]; 323.2 [45.8]), total thiol (409.6 [70.2]; 363.5 [46.1]), and disulfide values (23.6 (5.4); 20.2 (4.3)) were significantly higher in group 1 than group 2, while the median (interquartile range [IQR]) values of IMA (0.89 (0.85-max 0.92); 0.85 (min 0.82-max 0.879) were significantly higher in group 2 than group 1 (P < 0.05). Conclusions: As general anesthesia may cause a higher degree of oxidative stress, selecting the appropriate anesthetic technique may be especially important for risky pregnancies in which increased oxidative stress in the mother and baby may be critical for the outcome.